Pengembangan Laboratorium Bisnis Digital Sebagai Pra Inkubator Bisnis Untuk Meningkatkan Kreativitas Kewirausahaan Mahasiswa FE Unimed - Novita Indah Hasibuan; Danny Ajar Baskoro; Alfi Nura (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2023)
This study aims to develop a Digital Business Laboratory as a pre-business incubator. The research was conducted in a series of stages, including needs identification, mentor mobilization, module development, in-lab training, orientation, and assessment. The initial stage of the research was identification, in which students were given the opportunity to identify their wants and expectations regarding research and entrepreneurship programs. The next stage is mentor mobilization, in which experienced mentors from industry and academia are involved. Next, a module was developed, which included learning materials related to the managerial, financial, and marketing aspects of the business. Training in the laboratory was conducted using the prepared e-modules, supported by statistical software, social media, and adequate hardware. The results of this study indicate that the Digital Business Laboratory contributes significantly to enhancing the entrepreneurial creativity of student of the Faculty of Economics, State University of Medan. Students gave a positive assessment of the insights and knowledge provided by the laboratory, as well as its influence on understanding the managerial, financial, and marketing aspects of business. The use of media, such as Google Trends and social media analysis, is also considered beneficial in gaining relevant market insights. In addition, training in the laboratory and the assessments conducted provided a clear picture of students' entrepreneurial abilities. Students also felt that the Digital Business Laboratory met their expectations as a pre-business incubator and helped them develop skills and knowledge that could be applied in the business world.